Comparative Study of the Effects of Machine Parameters on DFIG and PMSG Variable Speed Wind Turbines During Grid Fault - Okedu, Kenneth E.; Al Tobi, Maamar; Al Araimi, Saleh (Frontiers in Energy Research, 2021)
This study investigates the transient performance of two variable speed wind turbines (VSWTs), namely doubly fed induction generator (DFIG) and the permanent magnet synchronous generator (PMSG), that are widely employed in wind energy conversion, considering their machine parameters. The machine parameters of both wind turbines were changed considering different scenarios, while keeping other parameters constant, to study the behavior of the wind generators. This study was carried out using the same operating conditions of rated wind speed, based on the characteristics of both wind turbine technologies. The wind turbines were subjected to a severe three phase to ground bolted fault to test the robustness of their controllers during grid fault conditions. Efforts were made to carry out an extensive comparative study to investigate the machine parameters that have more influence on the stability of the different wind turbines considered in this study. Simulations were carried out using power system computer-aided design and electromagnetic transient including DC (PSCAD/EMTDC). Effective machine parameter selection could help solve fault ride-through (FRT) problems cost-effectively for both VSWTs, without considering the external circuitry of and changing the original architecture of the wind turbines.